Osteoradionecrosis of the Hyoid Bone: A Systematic Review - Quentin H. Drane, BS; Andrea Ziegler, MD; Eric J. Thorpe, MD (Advances in Radiation Oncology)
Purpose: Osteoradionecrosis (ORN) is a serious complication following radiation therapy (RT) for head and neck cancers, commonly affecting the mandible, but is less understood when involving the hyoid bone. Methods and Materials: A literature review through PubMed and Scopus identified 16 relevant articles. Patient characteristics, presentation, imaging findings, management, and outcomes are highlighted. Results: The review found 40 cases of hyoid bone ORN, with an average patient age of 60.0 years. Most patients were male (87.5%) and had oropharyngeal tumors (77.5%). The average RT dose was 66.2 Gy, and ORN typically developed 27.6 months after RT. Patients receiving concurrent radiation and chemotherapy were more likely to need surgery compared with those treated with RT alone (80% vs 30%, P = .0042). Conclusions: While rare, hyoid bone ORN may become more common with increasing rates of oropharyngeal cancers. Clinicians should be aware of presenting symptoms and possible complications and be familiar with a thorough work-up and treatment.